The Effectiveness of Zakat, Islamic Corporate Social Responsibility, and Sharia Supervisory Board in Driving the Financial Performance of Islamic Banks: Case Study in Indonesia (UIN Sunan Kudus, 2025)
Thisiresearch sight to examined the influenced of zakat, Islamicicorporateisociali responsibility, and the Sharia supervisory board on financial performance, as appraised by return on assets (ROA), in Islamic commercial banks in Indonesia during the period 2018-2023. This study employs a causality research design with a quantitative approach. The sampling method used is purposive sampling. The samples consist of 42 banks listed with the financial services authority. Secondary data sourced from the annual reports of each Islamic commercial bank in Indonesia are utilized in this study. Panel data regression analysis is applied as the data analysis technique. The study's discovery reveals that zakat has a positive impact on financial performance, whereas Islamic corporate social responsibility and the Sharia supervisory board do not influence financial performance. Keywords: